Mixed sorghum and forage cactus silage: composition, digestibility, fermentation, and losses - Oliveira, Palloma Vitória Carlos de (2023)
The production of mixed silages can be an essential strategy for storing and processing feed for ruminants in arid and semi-arid regions. This study aimed to evaluate the effect of inclusion levels of forage cactus in sorghum silage on chemical-bromatological composition, losses, in vitro digestibility, and fermentative profile. Sorghum silages were produced by adding 0, 10, 20, 30, and 40% forage cactus based on natural matter. Experimental silos were filled with the mixtures and hermetically sealed. The silos were opened after 34 days of fermentation, and the samples were analyzed for composition, digestibility, fermentative profile, and losses in silage. The inclusion of forage cactus presented a negative quadratic influence (P < 0.05) on the contents of dry matter (DM), ether extract, neutral detergent fiber, acid detergent fiber, and cellulose of sorghum silage. The DM concentration decreased from 35.83 to 25.43% for the control treatment (0%) to the 20% treatment, followed by stabilization at values close to 26 ± 1% in subsequent levels. Digestibility in vitro and the total digestible nutrients of the silages increased linearly (P < 0.05) with the inclusion of forage cactus. However, there was a linear increase (P < 0.05) of pH, ammonia nitrogen, acetic acid, and butyric acid with the inclusion of forage cactus, reaching values indicative of the limitation of the fermentation process from the level of 20% inclusion. Including forage cactus in sorghum silage did not affect (P > 0.05) losses by gases, effluents, and DM recovery from silage. Adding up to 10% of forage cactus can benefit chemical-bromatological characteristics, digestibility, and fermentation of sorghum silage.